O papel da reforma tributária na eficiência da administração pública municipal - Marcos Vinicius Montalvão da Silva (Revista ft, 2026)
The Brazilian tax reform changed the structure of consumption taxation by introducing the Tax on Goods and Services and the Social Contribution on Goods and Services, with implications for municipal revenue collection, financial autonomy, and tax enforcement. This study aimed to analyze how these changes could influence the efficiency of municipal public administration, considering revenue distribution and the adaptation of tax controls. A qualitative, descriptive, and exploratory narrative literature review was conducted and supplemented by documentary analysis. Scientific articles published between 2020 and 2026 were consulted in specialized databases and journals, together with current constitutional and statutory legislation. Review articles, dissertations, theses, and conference papers were excluded. The analysis indicated that noncumulative taxation and the destination principle may reduce distortions and promote revenue redistribution, although their effects vary according to each municipality’s economic structure and institutional capacity. Aggregate revenue neutrality does not ensure local stability, as municipalities dependent on the Service Tax, transfers derived from the Tax on the Circulation of Goods and Services, or intergovernmental funds remain exposed to temporary losses. Data integration, electronic tax documents, coordinated enforcement, and staff training were identified as conditions for administrative efficiency gains. It was concluded that the reform may improve municipal tax administration, provided that equalization mechanisms, accounting planning, and technological infrastructure reduce disparities and preserve the financing of public services during the transition between tax systems, while accounting for differences in municipal size, own-source revenue, and dependence on intergovernmental transfers.